Valuasi Saham Multi-Metode pada Subsektor Pelabuhan dan Layanan di Indonesia - Pujiono; Anisah Firli (Journal of Accounting, Management, and Economics Research (JAMER), 2026)
This study addresses a gap in prior valuation research, which primarily relies on a single valuation method or a combination of DCF–FCFF and Relative Valuation, providing limited evidence on the consistency of multiple valuation approaches within the same industry. It evaluates the intrinsic value of Marine Port and Services Subsector companies listed on the Indonesia Stock Exchange using three approaches: Discounted Cash Flow–Free Cash Flow to Firm (DCF–FCFF), Residual Income Model (RIM), and Relative Valuation based on Price Earnings Ratio (PER), Price to Book Value (PBV), and Enterprise Value to EBITDA (EV/EBITDA). Secondary data were collected from the 2018–2024 financial statements and annual reports of PT Indonesia Kendaraan Terminal Tbk (IPCC), PT Jasa Armada Indonesia Tbk (IPCM), PT Meratus Jasa Prima Tbk (KARW), and PT Nusantara Pelabuhan Handal Tbk (PORT). The analysis includes cash flow projections, cost of capital estimation, and firm and equity valuation. The findings are consistent across all valuation methods. IPCC and IPCM are identified as undervalued because their intrinsic values exceed market prices, whereas KARW and PORT are overvalued because their intrinsic values fall below market prices. These results indicate that combining multiple valuation approaches provides a more robust basis for investment decision-making.